A background digital calibration of split-capacitor 16-bit SAR ADC with sub-binary architecture. Issue 9 (September 2015) - Cao, Chao; Ye, Qian; Zhu, Zhangming; Yang, Yintang
Abstract The paper introduces a sub-binary architecture in 16-bit split-capacitor successive-approximation register (SAR) analog-to-digital converters (ADCs). The redundancy in sub-binary capacitors array provides ways to correct the dynamic errors in conversion procedure with a smaller overall conversion time. So the redundancy can be used to solve the mismatch or parasitic problems in split-capacitor CDAC SAR. A background digital calibration method with perturbation is utilized to calibrate the conversion errors. The behavioral simulation and measured results show that the 16-bit SAR ADC performance can be improved after the digital calibration. The prototype was fabricated in 0.18 μm CMOS process. The INL are −6/7.813 LSB, the DNL are −0.925/1.313 before calibration. After calibration, the INL are −0.813/0.938, the DNL are −0.625/0.688. The measured ENOB is 11.42 bit and SFDR is 79.95 dB before calibration, while the ENOB is 14.46 bit and SFDR is 95.65 dB after calibration.